An improvement of Energy Efficient Multipath Routing Node Management Techniques for MANET - Rajeshkanna, R.; Saradha, DrA. (IJRDO -Journal of Computer Science Engineering, 2016)
A mobile ad hoc network (MANET) is a continuously self-configuring, infrastructure-less network of mobile devices connected wirelessly. Each device in a MANET is free to move independently in any direction, and will therefore change its links to other devices frequently. In such networks, the mobile nodes may dynamically enter the network as well as leave the network. Due to the restricted transmission range of wireless network devices, multiple hops are usually needed for a node to exchange information with any other node in the network. A joint routing and energy allocation plan is developed which stabilizes the system and provides surrounded average delay guarantees whenever the input rates are within this capacity segment. This paper considers jointly optimal design of cross layer congestion control, routing overhead and Throughput for Mobile ad hoc networks